Handbook of structural stability. Part 1, - Gerard, George; Becker, Herbert, 1918- (National Advisory Committee for Aeronautics, 1957)
The various factors governing buckling of flat plates are critically reviewed and the results are summarized in a comprehensive series of charts and tables. Numerical values are presented for buckling coefficients of flat plates with various boundary conditions and applied loadings. The effects of plasticity are incorporated in non dimensional buckling charts utilizing the three-parameter description of stress-strain curves.
NACA TN No. 3781.
Keywords: Structural analysis (Engineering); Stability.; Plates (Engineering); Buckling (Mechanics); Loads (Mechanics); Strains and stresses.; elektronické knihy; electronic books